Stomach contents and notes on the reproduction of the Onefin Skate Gurgesiella dorsalifera (Chondrichthyes: Rajidae) off Southern Brazil - Rincon, Getulio [UNESP]; Vaske Junior, Teodoro [UNESP]; Vooren, Carolus M. [UNESP] (Sociedade Brasileira de Ictiologia, 2008)
A raia endêmica brasileira de profundidade Gurgesiella dorsalifera é uma espécie rara e de pequeno porte recentemente descrita nos anos 80. Não há informações disponíveis sobre a sua biologia e sua distribuição geográfica extremamente restrita tem sido utilizada para classificá-la como uma espécie vulnerável sob os critérios da Lista Vermelha da IUCN. Vinte e quatro espécimes (larguras de disco entre 115-207 mm) foram capturados na costa do sul do Brasil na região do Cabo de Santa Marta Grande (Estado de Santa Catarina) por arrasto de fundo de profundidade (430-524 m). A análise dos conteúdos estomacais revelou um aparente oportunismo predatório sobre juvenis de Urophycis brasiliensis (IRI = 6944) com comprimento total médio de 21 mm, seguido por crustáceos misidáceos (IRI = 2938), teleósteos não identificados (IRI = 1969), o copépode Bradyidius plinioi (IRI = 393) e crustáceos decápodes (IRI = 297). Uma fêmea adulta com 207 LD apresentava dois ovos, um em cada útero.

The Brazilian endemic deep-water onefin skate (Gurgesiella dorsalifera) is a rare small species recently described in the 80's. No biological information is available on this species and its extremely restricted geographic distribution has been used to classify it as a vulnerable species under IUCN red list criteria. Twenty four specimens (115 to 207 mm disc width) were captured off southern Brazilian coast at the region of Cape Santa Marta Grande (State of Santa Catarina) by deep-water otter trawl (430-524 m). The analysis of stomach contents revealed an apparent opportunistic predation on juveniles of Urophycis brasiliensis (IRI = 6944), with an average total length of 21 mm, followed by mysidaceans (IRI = 2938), unidentified teleosts (IRI = 1969), the copepod Bradyidius plinioi (IRI = 393), and decapod crustaceans (IRI = 297). One mature female with 207 mm DW had two egg cases in its uteri.
Keywords: Elasmobranch; Deep-water; Batoidea; Rajiformes